Debt, Growth Opportunities and Investment of Listed Firms in Vietnam - Tan, Dang Van; Tuyen, Huynh Thi; Nhi, Le Thi Thao; Quyen, Tran Ly Hoang; Anh, Nguyen Duy; Liem, Nguyen Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
This study examines the simultaneous relationship between debt and debt maturity structure of firms with different growth opportunities. In addition, we analyze the effects of these factors on the investment of Vietnamese-listed firms in the period 2010-2020. Using the 3SLS regression model, the results show a negative relationship between debt and debt maturity structure, supporting the underinvestment hypothesis. However, when firms have higher growth opportunities, the relationship between the two factors turns positive, supporting the hypothesis of liquidity risk. The results of using the System GMM model to examine the impact of debt, debt maturity, and growth opportunities on investment further confirm the above findings. These findings have important implications for managers in making investment decisions.